Argenis - Barclay, John 1582-1621 (Utrecht Elsevier, 1630)
Argenis tells the story of the religious conflict in France under Henry III of France and Henry IV of France, and also touches on more contemporary English events, such as the Overbury scandal. The tendency is royalist, anti-aristocratic; it is told from the angle of a king who reduces the landed aristocrats' power in the interest of the "country", the interest of which is identified with that of the king. (Wikipedia)
Historical allegory
contains an index of terms and a 'tabula nominum fictorum'
originally published in Paris, 1620; first edition by Elsevier published in 1627
name of previous owner crossed out on flyleaf and tp
Editio novissima. Cum clave, hoc est nominum propriorum elucidatione hactenus nondum edita.
Keywords: 17th Century (1601-1700); History; Novel; Scotland; United Kingdom